Preliminary crystallographic study of bluetongue virus capsid protein, VP7. - Basak, A; Stuart, D; Roy, P (1992)
Bluetongue virus serotype 10 (BTV-10) VP7, expressed by insect cells infected with the recombinant baculovirus, has been purified and crystallized. Two crystal forms suitable for X-ray analysis have been obtained. Type I crystals belong to space group P6(3)22 with a = b = 95.2 A, c = 181.0 A, alpha = beta = 90 degrees gamma = 120.0 degrees, and contain a single subunit in the crystallographic asymmetric unit. They diffract to dmin = 3.0 A. Type II crystals belong to space group P2(1) with a = 69.4 A, b = 97.1 A, c = 71.4 A, beta = 109.0 degrees, and contain a trimer in the crystallographic asymmetric unit. They diffract to dmin = 2.1 A. These results, together with solution studies, show that the molecule is a trimer.